1985
DOI: 10.1002/aic.690310214
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy solution theory of adsorption using Flory‐Huggins activity coefficient equations

Abstract: New equations for the physical adsorption of gases on solids have been developed based on the vacancy solution model of adsorption in conjunction with the Flory-Huggins activity coefficient equations. The isotherm equation contains three regression parameters: a Henry's law constant, the limiting amount of adsorption, and a gas-solid interaction term. Pure-gas data over a range of temperature can be correlated using only five parameters. Gas-mixture equilibria can be predicted using only the parameters obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
124
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(125 citation statements)
references
References 18 publications
0
124
0
1
Order By: Relevance
“…These are listed in Table 3. (The original nomenclature of Cochran et al, 1985, has been preserved.) Figure 6 clearly indicates that this model correlates the experimental data quite well.…”
Section: Equilibrium Isothermsmentioning
confidence: 99%
See 2 more Smart Citations
“…These are listed in Table 3. (The original nomenclature of Cochran et al, 1985, has been preserved.) Figure 6 clearly indicates that this model correlates the experimental data quite well.…”
Section: Equilibrium Isothermsmentioning
confidence: 99%
“…Also illustrated in Figure 6 are correlations of the pure component data obtained with the Flory-Huggins vacancy solution model (FH-VSM) of Cochran et al (1985). Computer algo- rithm AD3 of the API Technical Data Book (Danner and Daubert, 1985) was used to conveniently regress the proper model parameters.…”
Section: Equilibrium Isothermsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Flory-Huggins form of the Vacancy Solution Model (FH-VSM) isotherm equation (Cochran et al, 1985a) for a pure adsorbate was found to fit the individual isotherm data well. The pure component isotherm equation is: A H ) in the above equations.…”
Section: Equilibrium Measurementsmentioning
confidence: 99%
“…Among the theories widely used for adsorption are the Langmuir model, ideal adsorbed solution (IAS) theory , heterogeneous ideal adsorbed solution (HIAS) (Myers, 1987), vacancy solution model (VSM) Cochran et al, 1985), theory of volume filling micropores (TVFM) (Dubinin, 1966), twodimensional equations of state model (2-D EOS) , and the simplified local density (SLD) model . In general, all the models work well for low-pressure adsorptions.…”
Section: Introductionmentioning
confidence: 99%